Transformation of the political regime in Ukraine in the times of independence: stages and features - Skrypniuk, Oleksandr; Melnykovych, Mykhailo; Strunevych, Oleksandra; Kubko, Andrii; Saranov, Sergiy (Amazonia Investiga, 2022)
The purpose of the article is to study the peculiarities of the transformation of the political regime in Ukraine at different historical stages of its independence. The subject of the study is the political regime of independent Ukraine. The research methodology includes the following methods: transitological, normative and value, sociological, comparative, systemic, structural and functional, neo-institutional. Results of the research. The approaches to the concept of political regime and its varieties are analyzed. The stages of its transformation in Ukraine are highlighted and it is determined that they are “tied” to the person of the president. The peculiarities of political regime of the times of independence during the passage of each of the cycles are established. Practical meaning. Based on the features of the political regime in independent Ukraine during the periods of rules of different presidents and in various stages, we conclude that the political regime in our country has all the signs of a hybrid one, and Ukraine is a "partially free country". Value/originality. It is proven that the decentralization of management in Ukraine multiplied by the intensification of political competition, the implementation of European values and the improvement of legal awareness and culture of our citizens could become a reliable foundation for the formation of a democratic Ukrainian society.